Activity profile of world-class professional surfers during competition: A case study - Mendez-Villanueva, A.; Bishop, D.; Hamer, P. (The Journal of Strength and Conditioning Research, 2006)
The activity profile of men's competitive surfing was investigated during an international contest. Forty-two male surfers were filmed during 42 elimination heats. Surfers' activities were classified into 1 of 4 distinct categories (paddling, wave riding, stationary, and miscellaneous). The surfers were paddling and stationary 51 % (25-70 %) and 42 % (23-72 %) of the total time, respectively. Wave riding accounted for 4 % (2-7 %) of the total time, whereas miscellaneous activity accounted for the remaining 2 % (0.1-6 %) of the total time. The frequency (average number of motions in a heat) of each activity was 26 for paddling (15-37); 17 for stationary (10-26); 5 for wave riding (2-8); and 6 for miscellaneous activity (1-13). The mean duration lengths of the activities were 30.1 seconds (1-286 seconds), 37.7 seconds (1-413 seconds), 11.6 seconds (1-44 seconds), and 5 seconds (1- 31 seconds) for paddling, stationary, wave riding, and miscellaneous activities, respectively. Most of the paddling bouts (60%) were performed at time intervals of between 1 and 20 seconds. Approximately 50 % (50.9 %) of the rest intervals were between 1 and 20 seconds in duration. The results showed that surfing is an intermittent activity characterized by a large variability and random distribution of each parameter analyzed. This information can be used to assist in the development of fitness training programs and physiological testing for competitive surfers.